The Factors Affecting Education Quality Assurance Operations within the Educational Schools under the Office of Uthai Thani Primary Educational Service Area 1 - Glankhetkij, Benjarat (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Quality assurance within educational institutions is a process that must be carried out systematically and continuously. In addition to directly improving the educational management of educational institutions, the results of the educational quality assessment are also used as linked evidence to support external quality assessments. Thus, the objectives of this research were 1) study the level of factors affecting school’s internal quality assurance operations. 2) study the level of school’s internal quality assurance operations. 3) to study the relationship between the school’s internal quality assurance operation, and 4) to create the predicted equation of factors affecting the operation of the school’s internal quality assurance operation. Methodology: The sample consisted of 242 administrators and teachers and randomized by sample random sampling. The research tools were the questionnaires regarding the factors affecting school internal quality assurance operation and the questionnaires regarding the level of school internal quality assurance operation with a reliability of 0.97. The statistics used for data analysis were mean, standard deviation, Pearson correlation coefficient and stepwise multiple regression analysis.Results: (1) The levels of factors affecting school’s internal quality assurance operations overall were at a high level. According to each aspect leadership, communication, and personnel, respectively. (2) The levels of the school’s internal quality assurance operation overall were at a high level. According to each aspect, it was at a high-level preparation of followed by the setting of educational standards of school, and preparation development plans of educational institutions that focus on quality in accordance with educational standards, respectively. (3) The relationship between the factors affecting a school’s internal quality assurance operations and implementation of educational quality assurance within educational schools for positive relationships overall was at a very high level (rxy = 0.85). With the statistically significant at the .01 level. and 4) The results of creating an equation school’s internal quality assurance operation are the environmental factors of organizational atmosphere, the organizational structure, the technology, the budget, and the leadership affecting the school’s internal quality assurance operation with statistical significance at .05 level. The predicted factors that affected the school’s internal implementation of quality assurance were 73 % accurate. Furthermore, the equation prediction was as follows: The predicting equation of raw scores was: = 0.93 + 0.22(X4) + 0.15(X3) + 0.18(X5) + 0.16(X8) + 0.09(X1) The predicting equation of standard scores was: = 0.26(Z4) + 0.19(Z3) + 0.23(Z5) + 0.20(Z8) + 0.12(Z1) Conclusion: The study reveals that the school’s internal quality assurance operations, influenced by factors such as leadership, communication, and personnel, are consistently at a high level. Additionally, the effective implementation of educational quality assurance is positively associated with these factors, with significant contributions from environmental elements like organizational atmosphere, structure, technology, budget, and leadership, demonstrating a predictive accuracy of 73%. This underscores the comprehensive and impactful nature of internal quality assurance measures within educational institutions.